Characteristic Description Of Patients With Obstructive Ileus Inap In Hospital IBN Sina Makassar 2023 - Fhadila Srikastiwi; Sulfikar Rusdam; Abdul Mubdi (Jurnal EduHealth, 2025)
Gastrointestinal tract disease is one of the causes of death in the world . Obstructive ileus is a condition that causes intestinal contents to be unable to pass through the intestinal lumen as a result of a blockage or mechanical obstruction in the intestinal lumen. This study reviews is to evaluate the characteristics of inpatient obstructive ileus patients at Ibnu Sina Hospital Makassar in 2023. This study uses a quantitative analysis research type with a cross-sectional approach by collect secondary data in the form of patient medical data records . The population in this study were all patients diagnosed with Obstructive Ileus disease at Ibnu Sina Hospital Makassar in 2023. By using the inclusion criteria , 30 people were determined to be samples . Based on the results of the study, it was concluded that the frequency of obstructive ileus sufferers based on age was highest in the age range of 45-59 years , the frequency of obstructive ileus sufferers based on gender was male, based on etiology , the most was adhesion , based on symptoms , the most was abdominal pain , based on support examinations , the most was plain abdominal photo 3 positions , based on the extent of obstruction , the most was partial obstruction , based on the location of obstruction , the most was low , based on management , the most was operative action , and based on outcome ( patient condition after hospitalization ) in obstructive ileus patients , the patient gone home in better condition . This evaluation can provide a picture of the characteristics of obstructive ileus patients to journal readers.